Synthesis and Characterization of La1-xMxTOy AND Y1-xMxTOy (M=Ca, Sr; T=Ti, Nb) Materials for Solid Oxide Fuel Cells - Gill, Jasmeet Kaur (My University, 2012)
The significant progress in the research and development of solid oxide fuel cells (SOFCs) has lead them to achieve the ultimate goal of commercialization. Solid oxide fuel cells are the most efficient devices for conversion of chemical fuels directly into electrical power. All over the world, lot of research is being carried out to search new electrolyte materials which have good thermal, structural stability in working atmosphere of SOFCs. Pyrochlore compounds (A2B2O7) can be used as solid electrolyte in solid oxide fuel cell. These compounds show order and disorder transition due to disordering in cations and /or anions. The magnitude of this disordering depends on the ionic radii difference between cations at the A and B sites. Interchangeability of A and B cations enhances the formation of anion Frankel defects which leads to good ionic conductivity in these systems. Basically, pyrochlore compounds are inherent ionic conductors whose properties may be altered by changing the processing conditions and doping of different elements on various sites. Yttrium titanate, Y2Ti2O7, is an important member of the pyrochlore family because it exhibits various properties which make it suitable for potential applications in different fields. Yttrium titanate (Y2Ti2O7) exhibits n-type conductivity at lower partial pressure of oxygen (pO2) while oxide ion conductivity was observed at high oxygen pressure. In the present work, it has been planned to investigate the effect of systematic doping of SrO, CaO for Y2O3 as well as La2O3 in Y2Ti2O7 and La2Ti2O7 system. Different concentration of Sr2+ and Ca2+ doping was chosen to find the solid solubility limit and its affect on conductivity. The results are discussed in light of oxygen vacancies, order and disorder transitions using electrical conductivity, X-ray analysis, Fourier Transform-Infrared Spectroscopy, thermal expansion coefficient (TEC) and scanning electron microscope (SEM) in-order to check their suitability for Solid Oxide Fuel Cells (SOFC). Moreover, LaNbO4 system has also been studied by many research groups to check its applicability and suitability as a potential electrolyte candidate for SOFC. LaNbO4 based materials are stable in CO2/H2O atmosphere and exhibits conductivity nearly 10-3 Scm-1. It was observed that partial substitution of La by Ce, Pr and Nb by Mn, W, Cr in LaNbO4 system exhibited good electronic conductivity. The maximum value of conductivity reported for acceptor doped LaNbO4 system is of 8 x 10-4 Scm-1 at 900°C in wet hydrogen. Recently, acceptor doped (Ca, Sr)LaNbO4 system which are stable in operating atmospheres have been reported as candidates for proton conducting electrolytes and these materials were hence, chosen for the present studies. The effect of acceptor doping (Sr, Ca) on A-site of ABO4 (A=La, Y) materials were further investigated. The entire work in this thesis is presented in five chapters. Chapter 1 deals with background and fundamentals of solid oxide fuel cell and their components. These are described in first section of the chapter. The various electrolyte materials exhibiting fluorite, perovskite and pyrochlore based structures are discussed in detail. The mechanism of ion conductivity which is the key feature of the solid electrolytes is given. Further, effect of doping on electrical conductivity is explained in detail. In addition to this, a comparison between electrolytes based on proton conducting materials and oxide ion conductors have been investigated. Moreover, applications of solid electrolytes in different areas are also presented. Chapter 2 gives a detailed account of the literature survey in context of pyrochlore systems. Since doping plays an important role in case of titanate pyrochlores A2Ti2O7 (A=Y), the role of dopants on the properties of pyrochlore structure is described in first section of the chapter. The electrical, thermoelectric, optical, structural properties and thermal conductivity of Y2Ti2O7 have been investigated extensively by various researchers. Perovskite materials have also been the subject of great deal of research for SOFC electrolyte applications. In addition to oxide ion conducting materials, proton conducting oxides are also discussed as electrolytes in fuel cells. Chapter 3 describes about experimental procedure followed in the present work. On the basis of literature survey, La1-xMxTOy and Y1-xMxTOy (M=Ca, Sr; T=Ti, Nb) system with x=0, 0.1, 0.2, 0.3, 0.4 were synthesized by solid state reaction method at different sintering temperature and processing conditions. The as prepared samples were characterized by different characterization techniques. In addition to this, the interaction study of two systems Y2Ti2O7 (electrolyte) and 40SiO2.30BaO.20ZnO.10Y2O3 based glasses have been done for study of chemical interactions between them to understand the kinetics of the formation of different crystalline phases with respect to the heat treatment temperature and duration. Chapter 4 deals with results and discussions of as prepared samples. The chapter is divided in five sections; in the first section the effect of systematic doping of Sr2+ and Ca2+ for Y3+ in Y1-xMxTiOy (M=Ca, Sr) system with x=0, 0.1, 0.2, 0.3, 0.4 was chosen to find the solid solubility limit and its affect on conductivity. The results are discussed in light of oxygen vacancies, order and disorder transitions using electrical conductivity, X-ray analysis, FTIR, TGA, TEC and SEM in-order to check its suitability for solid oxide fuel cells (SOFC). Second, third and fourth sections comprises of the effect of systematic doping of Sr2+ and Ca2+ for La3+ in La1-xMxNbOy (M=Ca, Sr) system, Y3+ in Y1-xMxNbOy (M=Ca, Sr) system, La3+ in La1-xMxTiOy (M=Ca, Sr) system with x=0, 0.1, 0.2, 0.3, 0.4 respectively. Fifth section comprises of the chemical interaction study between candidate glass sealant (40SiO2.30BaO.20ZnO.10Y2O3) and Ca2+ doped Y2Ti2O7 system. The selection of Ca2+ doped pyrochlore is based on its better thermal stability and presence of Y2O3 in both the samples of glass sealant and electrolyte. The purpose of this study was to understand the kinetics of the formation of different crystalline phases with respect to the heat treatment temperature and duration. Chapter 5 summarizes the results of all the experiments conducted for the doping of Sr2+ and Ca2+ viz Y1-xMxTiOy, La1-xMxNbOy, Y1-xMxNbOy, La1-xMxTiOy (x=0, 0.1, 0.2, 0.3, 0.4) systems. The overall conclusion shows that doping of Sr2+ and Ca2+ plays very crucial role to increase the disordering as well as oxygen vacancies leading to increase in conductivity values of Y2Ti2O7 system. On the other hand, it is found that higher doping concentration leads to secondary phase formation which inhibits the grain growth that ultimately reduces density with increase in porosity. Moreover, it is observed that effect of Ca2+ doping in Y2Ti2O7 system is more effective than Sr2+ doping in Y2Ti2O7 system due to occurrence of higher disordering leading to decrease in density with increase in porosity. On the other hand, XRD patterns of Sr2+ and Ca2+ doped LaNbO4 samples indicate the formation of secondary phase with its increasing volume fraction. It is observed that La0.95Sr0.05NbO4 phase is more conducting than LaNbO4 ¬phase. A major conductivity difference observed in La1-xMxNbOy system with x=0.4 i.e., 1.01x10-1 Scm-1 shows that this sample exhibits higher vacancies which provide path for ion conduction. The UV visible results also show the drastic change in band gap of this particular sample ~ 2.6 eV. In addition to above system, the effect of systematic doping of SrO and CaO for Y2O3 in YNbO4 system was also studied. It was observed that the undoped sample exhibit single phase i.e., YNbO4. The doping of Sr2+ in present system leads to secondary phase formation such as Sr2Nb2O7 and SrNb2O6. The formed secondary phases enhance the electrical conductivity by five orders of magnitude. The interaction study between (Y1-xCax)2Ti2O7-x for x=0.1 and 40SiO2.30BaO.20ZnO.10Y2O3 glass results in formation of different crystalline phases such as Y2Ti2O7, BaZn(SiO4), Ca(SiO3) and SiO2. It is observed that the volume fraction of detrimental phase (SiO2) decreases with increase in duration of heat treatment of 100h. The overall interaction study indicate that the above system can be a good substitute for long hour operation of SOFC as compared to the existing one as there is no crack observed in the system though porosity exists. The TEC values are also of same order as required for SOFC. The suggestion for future scope is also given. At the end, the list of papers published, presented and communicated are also appended.
Doctor of Philosophy
Keywords: Ac Conductivity; Solid state reaction method; SEM; XRD; Thermal analysis; Pyrocholre